A proof of concept for a targeted enrichment approach to the simultaneous detection and characterization of rickettsial pathogens from clinical specimens - Paskey, Adrian C.; Schully, Kevin L.; Voegtly, Logan J.; Arnold, Catherine E.; Cer, Regina Z.; Frey, Kenneth G.; Blair, Paul W.; Clark, Danielle V.; Ge, Hong; Richards, Allen L.; Farris, Christina M.; Bishop-Lilly, Kimberly A. (Frontiers in Microbiology, 2024)
Infection with either Rickettsia prowazekii or Orientia tsutsugamushi is common, yet diagnostic capabilities are limited due to the short window for positive identification. Until now, although targeted enrichment had been applied to increase sensitivity of sequencing-based detection for various microorganisms, it had not been applied to sequencing of rickettsial pathogens in clinical samples. Additionally, hybridization-based targeted enrichment strategies had only scarcely been applied to qPCR of any pathogens in clinical samples. Therefore, we tested a targeted enrichment technique as a proof of concept and found that it dramatically reduced the limits of detection of these organisms by both qPCR and high throughput sequencing. The enrichment methodology was first tested in contrived clinical samples with known spiked-in concentrations of R. prowazekii and O. tsutsugamushi DNA. This method was also evaluated using clinical samples, resulting in the simultaneous identification and characterization of O. tsutsugamushi directly from clinical specimens taken from sepsis patients. We demonstrated that the targeted enrichment technique is helpful by lowering the limit of detection, not only when applied to sequencing, but also when applied to qPCR, suggesting the technique could be applied more broadly to include other assays and/or microbes for which there are limited diagnostic or detection modalities.